(untitled) (Annals of Medical Research, 2021)
Aim: The pathophysiology of coronary artery ectasia (CAE) has not been clear. Dyslipidemia is a serious cause for increasing the risk of coronary artery disease. The relationship between isolated CAE and dyslipidemia is unknown. We evaluated the triglyceride to high-density lipoprotein cholesterol ratio (Tg to HDLc) and dyslipidemia in patients with isolated CAE.Material and Methods: We included 60 patients and 70 controls with normal coronary arteries with similar baseline risk factors. Total cholesterol (Tc), high-density lipoprotein cholesterol (HDLc), low-density lipoprotein cholesterol (LDLc), triglycerides (Tg) levels were measured and Tg to HDLc ratio was calculated. Factors predicting CAE were analyzed.Results: When compared with the controls serum Tg level and Tg to HDLc ratio were significantly higher, HDLc level was significantly lower in the patients (p=0.001; p=0.004; p=0.001, an respectively). The multivariate logistic regression analysis revealed that Tg to HDLc ratio (OR:1.476, 95% CI 0.1199-1.817, p=0.001) was independent factor predicting isolated CAE. In the ROC curve analysis, Tg to HDLC ratio was found to be statistically significant with a cut-off point value of 4.2 was determined to predict isolated CAE [AUC=0.829, (95% CI, 0.752-0.906), p=0.001].Conclusion: Tg to HDLc ratio, HDLc and triglycerides were found to be independent factors predicting isolated CAE. These lipid parameters and Tg to HDLc ratio may be a valuable, easily accessible, non-invasive way of predicting the presence of isolated CAE.